LITERASI MEDIA : UPAYA MENYIKAPI TAYANGAN TELEVISI - Marfuah Sri Sanityastuti (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This essay discribes TV shows that can be enjoyed every day by everyone in this country , has been hypnotizing audiences with construction that has built to justify subjective as people’s needs and normative justification that TV shows did not violate the rules. This media literacy movement offers solutions in order to deal with the development of media , to form a balance, by giving the knowledge to the public that the media reality is constructed so that the reality is not actual reality of the real world. In fact, as a result of construction, nature of reality will be greatly influenced by the values, interests, ideology, and also the social, economic, and political. Society have critical intelligence in order to deal with the massiv influence of TV. They have ability to choose TV program that become their needs because watching is not automatically forced to obey things that has been watched. Community should be genius to construct and reproduct itself continuously to form a dignified civilization.